Impacts of longwall mining speeds on permeability of weakly cemented strata and subsurface watertable: a case study. Issue 1 (1st January 2021) - Zhang, Shizhong; Fan, Gangwei; Zhang, Dongsheng; Li, Shaodong; Chen, Mingwei; Fan, Yibo; Luo, Tao
Abstract: The negative impacts of underground longwall coal mining on water resources and ecological environment are associated with changing overburden permeability and subsurface watertable. For weakly cemented strata characterized by short diagenesis, low strength, easy swelling and mudding with water, overburden permeability and subsurface watertable are highly sensitive to the advancing speed of the longwall. In this paper, the longwall panel 21103 in Yili No.4 Coal Mine, Xinjiang, China, where weakly cemented strata exist in Jurassic and Palaeogene systems, was taken as the case to study the response of overburden permeability and subsurface watertable to different advancing speeds. Results show that there is a butterfly-shaped permeability-increasing area comprised of a trapezoid and double V-shaped subareas in overburden. Generally, the permeability curves of aquiclude are of double peaks. In shallow aquifer, there is an exponential decline in the maximum drawdown of watertable, while a linear decline in lateral influence range as the speed goes up. If constrained by the ultimate watertable drawdown still being able to sustain the regular growth of vegetative covers, the optimal minimum advancing speed of panel 21103 is determined as 8 m/d, which is demonstrated by field verification.